2020
DOI: 10.1057/s41291-020-00129-9
|View full text |Cite
|
Sign up to set email alerts
|

HRM practices in South Asia: convergence, divergence, and intra-regional differences

Abstract: South Asia is distinct from other parts of Asia and the rest of the world because of its unique political, legal, economic, and socio-cultural systems. Despite this uniqueness, human resource management (HRM) practices of the countries making up this region have not been subjected to sustained examination. This study aims to examine the HRM practices in six South Asian countries including Bangladesh, India, the Maldives, Nepal, Pakistan, and Sri Lanka by synthesizing the existing literature and to propose some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…, 2021). These implications are critical for employees during the COVID-19 pandemic in Bangladesh because employees in the country have also suffered from insufficient training and development opportunities and inequitable pay (Wajeeh-ul-Husnain et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…, 2021). These implications are critical for employees during the COVID-19 pandemic in Bangladesh because employees in the country have also suffered from insufficient training and development opportunities and inequitable pay (Wajeeh-ul-Husnain et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Prior researchers have emphasized the importance of law and legal systems in HRM practices (Wajeeh-ul-Husnain et al, 2020 (Ovanessoff and Plastino, 2017).…”
Section: Enhancing Efficiency In Recruitment and Selectionmentioning
confidence: 99%
“…Prior researchers have suggested that HRM policies are shaped by interests of stakeholders such as shareholders, management, employees, governments and trade unions and situation-related factors (Macini et al , 2020). Situational factors include law and societal values, labor market conditions, workforce characteristics, business strategies and management philosophy (Wajeeh-ul-Husnain et al , 2020). Additional factors include economic, governance-related factors, and legal systems (Leat and El-Kot, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…His systematic review included only empirical papers classified as A*, A, and B in the ranking of the Australian Business Deans Council (ABDC) and as Q1 or Q2 in the Scimago journal ranking (SJR). Next, Wajeeh-ul-Husnain et al (2020), in their systematic review of HRM research over 2 decades in South Asia, included 63 papers published in ABDC-ranked journals by using 9 keywords in several electronic databases. Their study included papers only on the core HR practices of indigenous private sector firms.…”
Section: Introductionmentioning
confidence: 99%